Cytotoxic activity of topotecan in human tumour cell lines and primary cultures of human tumour cells from patients. - Jonsson, E. (Nature Publishing Group, 1997)
The cytotoxic activity and cross-resistance pattern of the novel topoisomerase I inhibitor topotecan (Topo) were investigated in ten cell lines, representing different mechanisms of cytotoxic drug resistance, and in 218 fresh human tumour samples using the fluorometric microculture cytotoxicity assay (FMCA). Resistance to Topo in the cell lines was associated with expression of the multidrug resistance-associated protein (MRP), whereas the cell lines with P-glycoprotein (P-gp), topoisomerase II and glutathione-associated resistance did not show decreased sensitivity to the drug. Topo was more active in haematological than in solid tumour samples, but substantial activity was observed in carcinomas of the ovary and breast, sarcoma and childhood solid tumours. Cross-resistance to standard drugs representing different mechanisms of action was generally low in patient cells. The effect of Topo was better after longer exposure, but this time-dependent effect was largely abolished when adjustment for in vitro exposure was made. Topo showed activity both in proliferative and non-proliferative cell systems. The results indicate that Topo is insensitive to major mechanisms of resistance except for MRP. Proliferation does not seem to be necessary for the effect of Topo, and no superiority for protracted dosing schedules was observed. The results also suggest that, for example, leukaemias, lymphomas, sarcomas and childhood solid tumours may be suitable targets for future phase II trials.